EFEKTIVITAS PENGGUNAAN MEDIA APLIKASI MONDLY ARABIC DALAM MENINGKATKAN KETERAMPILAN MENYIMAK KOSAKATA BAHASA ARAB KELAS XI SMA MUHAMMADIYAH 2 SIDOARJO - Sholichah, Habibah; Ammar, Farikh Marzuki (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
The purpose of this research is to determine the increase in students' vocabulary listening skills before and after implementing the Mondly Arabic application and to determine the effectiveness of using the Mondly Arabic application for class XI students at SMA Muhammadiyah 2 Sidoarjo. This research uses a quantitative experimental research method with a one-group pretest-posttest design. The data collection method used in this research was observation, pretest and posttest questions, and documentation. Besides that, data analysis in this study used the normality test and paired samples t-test. The sample taken in this research was class XI.1 of SMA Muhammadiyah 2 Sidoarjo, totaling 34 students. From the results of research on increasing students' vocabulary through test questions, the pre-test average was 63.97 and the post-test average was 86.47. The calculated results of the paired samples t-test sig (2-tailed)<Research Alpha (0.000*<0.05), show the effectiveness of the Mondly Arabic application in improving students' vocabulary listening skills. This proves the significant effectiveness of using the Mondly Arabic application to improve students' Arabic vocabulary listening skills.